A study on valve timing optimization in si engines - Ly Vinh Dat; Tran Xuan Dung (Journal of Technical Education Science, 2017)
The study refers to simulation study that uses Matlab Simulink for SI engines. This research examines the effects of intake valve timing on the engine performance in order to propose methods for improving performance and fuel consumption efficiency in SI engines. The study has built a simulation model for SI engines successfullyto investigate the effects of valve timing on engine performance and fuel consumption at different engine speeds. The simulation results show that the used electromagnetic valve train, whose valve timing is optimized, can increase the engine performance in SI engines upto 33% and 34.7% higher for increasing torque, and the fuel consumption by 18.65%. Thus, the engine has got the optimal thermal efficiency, fuel consumption and engine performance.